2021
DOI: 10.1016/j.mayocp.2020.08.041
|View full text |Cite
|
Sign up to set email alerts
|

Kidney Microstructural Features at the Time of Donation Predict Long-term Risk of Chronic Kidney Disease in Living Kidney Donors

Abstract: Objective: To determine whether microstructural features on a kidney biopsy specimen obtained during kidney transplant surgery predict long-term risk of chronic kidney disease in the donor. Patients and Methods: We studied kidney donors from May 1, 1999, through December 31, 2018, with a follow-up survey for the results of recent blood pressure and kidney function tests (estimated glomerular filtration rate [eGFR] and proteinuria). If not recently available, blood pressure and eGFRs were requested from a local… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
44
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 26 publications
(47 citation statements)
references
References 39 publications
3
44
0
Order By: Relevance
“…However, the goal was to determine whether any definition of hypertension at the time of donation predicts long‐term risk of kidney disease regardless of whether interim events after donation also contribute to kidney disease risk. Donors who participated in the survey may also have recall bias; however, in a prior study we showed that there was an excellent correlation comparing serum creatinine from medical chart and reported from the survey at follow‐up from the same patient 46 …”
Section: Discussionmentioning
confidence: 77%
“…However, the goal was to determine whether any definition of hypertension at the time of donation predicts long‐term risk of kidney disease regardless of whether interim events after donation also contribute to kidney disease risk. Donors who participated in the survey may also have recall bias; however, in a prior study we showed that there was an excellent correlation comparing serum creatinine from medical chart and reported from the survey at follow‐up from the same patient 46 …”
Section: Discussionmentioning
confidence: 77%
“…As reported previously, self-reported data have been validated when compared to objective in available medical records. 17 , 23 The survey was not designed to assess for stone recurrence and not all SFs had medical records for review, thus stone recurrence during follow-up was not assessed.…”
Section: Methodsmentioning
confidence: 99%
“…The Aging Kidney Anatomy study cohort has detailed biopsy characteristics of kidneys in living donors and their long-term outcomes. 16 , 17 This cohort offers a unique opportunity to study the clinical and structural characteristics of donors with nephrolithiasis and their long-term outcomes.…”
mentioning
confidence: 99%
“…5 A recent study identified a low nephron number for age as predictor for long-term risk of chronic kidney disease after living kidney donation. 6 Whether reduced nephron number or cortical kidney volume, which has also been linked with post-donation kidney function 7,8 , are associated with a less pronounced post-donation increase in single-kidney GFR is unknown.…”
Section: Introductionmentioning
confidence: 99%